Cytoprotective Effect of Phenolic Extract from Brazilian Apple Peel in Insulin-Producing Cells - Yassin, Lorene S.; Alberti, Aline; Ferreira Zielinski, Acacio Antonio; da Rosa Oliveira-Emilio, Henriette; Nogueira, Alessandro (Current Nutrition & Food Science, 2018)
Background: The functional potential of the phenolic extract of apple peel in protecting insulin-producing RINm5F cells under conditions of stress induced by glucose is sparse. Objective: This study evaluated the in vitro protective effect of the phenolic extracts from apple peel (Gala and Fuji). Method: Insulin-producing RINm5F cells were induced by oxidative stress with glucose and hydrogen peroxide, which simulated cellular damage. Results: The Gala peel extract had the highest content of phenolic compounds (1299 mg CAE/kg) and in vitro antioxidant activity (14263 μmol TE/kg). At concentrations above 10 μg/mL the Fuji peel extract was cytotoxic, whereas the Gala peel extract (10 μg/mL) increased cell viability. The Gala peel extract showed the potential to protect cells under conditions of stress induced by glucose, with low intracellular production of superoxide. Under hydrogen peroxide, both extracts did not have a cytoprotective effect. Conclusion: The high antioxidant and cytoprotective activities of the apple peels indicated that they may convey health benefits and should be considered as a valuable source of antioxidants.
Keywords: Gala